The Implementation of Mind Mapping Towards Students’ Descriptive Writing Achievement in Junior High School - Jens Maritha Rai; Agustinus Bambang Setiyadi; Novita Nurdiana (English Language Education Study Program, 2024)
The research aimed to find out whether there is any significant improvement in students' writing achievement after they are taught with mind mapping technique in teaching writing of descriptive text and to find out which aspect of writing increased the most after the use of mind mapping technique. This research used quantitative research with one group pre-test and post-test design. The results showed that the mean score of the pre-test was 42.78 and the post-test score was 65.85 The gain score was 9.68. It could be seen from the significant value of the test, which was lower than alpha 0.00 < 0.05 and the t-value (15.820) was higher than t-table (1.7033). The statistically showed that there was a significant increased students' writing between the pre-test and the post-test after the students were taught by using mind mapping technique in writing skills. It was followed by content aspect with the gain 6.96 in which the aspect that increased the most. Therefore, it can be concluded that the digital mind mapping technique was effective for students' writing skills in descriptive text, particularly in content aspect.